2015
DOI: 10.1021/acs.accounts.5b00445
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Properties of Hybrid Perovskites

Abstract: Metal halide perovskites have come to the attention of the scientific community for the progress achieved in solar light conversion. Energy sustainability is one of the priorities of our society, and materials advancements resulting in low-cost but efficient solar cells and large-area lighting devices represent a major goal for applied research. From a basic point of view, perovskites are an exotic class of hybrid materials combining some merits of organic and inorganic semiconductors: large optical absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
148
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 50 publications
11
148
0
Order By: Relevance
“…182 Comprehensive modeling of the convoluted band edge absorption in CH 3 NH 3 PbX 3 has been carried out in a number of studies. 58,59,184,189,225,233 Excitonic and Coulomb-enhanced absorption are accounted for in Elliot's theory of Wannier excitons according to 234…”
Section: Chemistry and Dimensionalitymentioning
confidence: 99%
“…182 Comprehensive modeling of the convoluted band edge absorption in CH 3 NH 3 PbX 3 has been carried out in a number of studies. 58,59,184,189,225,233 Excitonic and Coulomb-enhanced absorption are accounted for in Elliot's theory of Wannier excitons according to 234…”
Section: Chemistry and Dimensionalitymentioning
confidence: 99%
“…The Rabi splitting of Ω = 200 meV determined here for CsPbBr 3 NWs is very similar to values from 2D layered organic-inorganic hybrid perovskite [31][32][33] or 3D CsPbBr 3 nanoplates [25] in DBR microcavities, suggesting that strong light-matter interaction is intrinsic to this class of materials. In perovskites, while an above gap excitation creates predominantly charge carriers at room temperature, [40,41] there is a strong excitonic resonance in absorption and fluorescence emission, with an exciton binding energy of ≈40 meV for CsPbBr 3 perovskite. The vacuum Rabi splitting measured for CsPbBr 3 NWs represents the highest value for inorganic semiconductor lasers where previous studies reported Ω up to ≈25 meV in the near-IR to visible region in, e.g., GaAs and CdTe, and up to ≈150 meV in the UV region for large bandgap materials, such as ZnO and GaN.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…38 The quantum confinement and high excitons binding energies are believed to increase the LED efficiency. 39 However, to date, such 2D perovskites have not been successfully integrated as the light emitting material into LEDs that can be operated at room-temperature. Green LEDs incorporating 2D PEA lead iodide [(PEA)2PbI4] were previously reported to function exclusively at liquid nitrogen temperatures, 40 thus precluding their practical applications.…”
mentioning
confidence: 99%